Study On Mechanical And Thermal Properties Of Fired Clay Brick From Five Different States In Malaysia - Razali, Sali Amirah (Universiti Sains Malaysia, 2018)
This research was to study the mechanical and thermal properties of fired clay brick from five different states in Malaysia. Mechanical properties are determined by the behaviour under applied forces using mechanical test. Thus, provides the basic for predicting behaviour of materials under different load condition and designing the components out of them. Thermal properties are those properties of a material which is related to its conductivity of heat. The quality of fired clay brick from different factory varies due to the different method of a manufacturing process. This is one of the main contributing factors for the problem which is to identify the best manufactured fired clay brick and how to improve the quality of the existing fired clay brick produced. Besides, the temperature often becoming the most important factor to maintain the optimum indoor thermal comfort when the humidity is kept at around 50% with absent of air movement. The experiment were conducted including water absorption test, compressive strength test, flexural test, thermal test, density test and non-destructive test Ultrasonic Pulse Velocity (UPV) of the fired clay brick from five different states. Based on the result obtained, the fired clay brick from Rantau Panjang, Kelantan shows the highest compressive strength than other fired clay brick. Besides, it has the higher flexural strength, and lower water absorption which tend to produce the good quality of brick. Moreover, the value of the hardness tests which Ultrasonic Pulse Velocity (UPV) was higher than other brick. The higher compressive strength and flexural of brick consists of low water absorption due to less porosity. As a result, the thermal conductivity decreases with decrease in density and increase in fired clay bricks porosity. As conclusion, the best quality of brick from five different states in Malaysia was brick from Rantau Panjang, Kelantan.